Analysis of Filling Machines in an Alcoholic Beverage Company at PT. Karunia Jaya Abadi Inds - Amiluhur, Theodorus Yohan; Islamiyah, Mufidatul (Jurnal Pengabdian Masyarakat, 2024)
Purpose: PT. Karunia Jaya Abadi Inds. is an industry that operates in the alcoholic beverage sector. To meet the increasing market demands for alcoholic beverages, the company switched to using robotic-based filling machines. Method: The methodology used in collecting data includes field reviews, consultations with field supervisors, consultations with lecture supervisors, and literature studies. Practical Applications: The aim of this research is to find out the specifications of the filling machine and to know the working principle of the filling machine at PT. Karunia Jaya Abadi Inds. Conclusion: The robotic-based filling machine is an innovation carried out by PT. Karunia Jaya Abadi Inds. This machine is Robo Filler type. The specifications of the filling machine include robot and controller, filling system, product delivery system, and utilities. In general, the working principle of the Robo Filler bottle is carried by a conveyor to a nozzle which will spray the product liquid according to the volume indicated on the control panel. The volume is controlled by a Coriolis flowmeter.